Disease Progression in Patients with Parkin‐Related Parkinson's Disease in a Longitudinal Cohort. Issue 2 (27th October 2020) - Sun, Yi‐Min; Yu, Hui‐Ling; Zhou, Xin‐Yue; Xiong, Wei‐Xi; Luo, Su‐Shan; Chen, Chen; Liu, Feng‐Tao; Zhao, Jue; Tang, Yi‐Lin; Liang, Xiao‐Niu; Yang, Yu‐Jie; Shen, Bo; et al.
ABSTRACT: Background: There was a paucity of follow‐up studies in the disease progression of early‐onset PD patients with Parkin mutations ( Parkin ‐EOPD). Here we conducted a longitudinal study to investigate the progression of motor and cognitive features of Parkin ‐EOPD patients. Methods: Genetic analysis was performed via target sequencing and multiplex ligation‐dependent probe amplification. Thirty patients carrying homozygous or compound heterozygous Parkin mutations with at least 2 follow‐up revisions were investigated as the Parkin ‐EOPD group. Fifty‐two patients with at least 2 follow‐up revisions, who did not have any known causative PD mutations, GBA or LRRK2 risk variants, a heterozygous Parkin mutation or 2 Parkin mutations without a segregation test, were defined as the genetically undefined EOPD (GU‐EOPD) group. A linear mixed‐effect model was implemented to evaluate longitudinal changes in motor symptoms and cognition. Results: At baseline, the Parkin ‐EOPD group had a lower Unified Parkinson's Disease Rating Scale score (UPDRS‐III) (off‐medication) than the GU‐EOPD group, without significant differences in cognition. A longitudinal study showed the estimated progression rate per year (standard error) of the UPDRS‐III score (off‐medication) was lower in the Parkin ‐EOPD group (0.203 [0.3162] points per year) than in the GU‐EOPD group (1.056 [0.3001] points per year). The difference in the UPDRS‐III score rate between the 2 groups was 0.853 (0.4183) ( P = 0.042). The Parkin ‐EOPD group showed better maintenance of spatial processing ability compared with the GU‐EOPD group ( P = 0.027). Conclusion: Parkin ‐EOPD patients showed a slower deterioration of motor symptoms and a better spatial processing ability than GU‐EOPD patients, which suggests that subtyping according to genetic features can help predict PD progression. © 2020 International Parkinson and Movement Disorder Society